Women in the marriage process in the light of the laws of Khammurabi (1792-1750 BC) and cuneiform texts - Hassan, Asst.Prof.Dr.Dr. Aram Jalal; Ramazan, Asst.Prof.Dr.Ziyar Siddiq (Sulaimani Journal for Humanities, 2026)
Women played a vital role in Mesopotamian civilization, and thus enjoyed a special status. Their responsibilities and legal rights were defined in legal texts during the Christian era. Secondly, specifically in the Code of Hammurabi, numerous legal articles (Laws 128-191) addressed women's affairs and circumstances, such as marriage and divorce, women's rights and responsibilities within the family, children, and other related matters. Generally, society can be divided, according to the Code of Hammurabi, into three social classes: the lowest class (oylum), the class of citizens or the poor (miskinnum), and the class of slaves (wardum). Naturally, women's rights existed within these three classes, and most of them fall under the category of rights, especially for women belonging to the poor or slave classes. This research focuses on the practice of marriage and polygamy, on the one hand, and identifies the obstacles that hindered marriage in ancient Babylonian society during the second millennium BCE, on the other. We have applied a special text on nails to the marriage contract, along with reading and translating it, with the aim of obtaining the rights of many women benefiting from their special rights after the completion of marriage.